PRAGMATICS IN DIGITAL COMMUNICATION: MEANING BEYOND WORDS - Kuchkarova Mukhayyo Abduvakhob kizi, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Abstract. The rapid growth of digital communication has transformed the ways people create, interpret, and exchange meaning. Unlike traditional face-to-face interaction, online communication often relies on text, emojis, memes, images, and other multimodal elements to convey intentions and emotions. As a result, understanding a message requires more than simply interpreting the literal meaning of words. This article explores the role of pragmatics in digital communication, focusing on how context, implicature, speech acts, emojis, and online discourse contribute to meaning-making. The study argues that digital communication has expanded the scope of pragmatic interpretation by introducing new communicative tools and practices. While these innovations enhance creativity and efficiency, they also create challenges related to misunderstanding, ambiguity, and intercultural communication. The article concludes that pragmatic competence is increasingly essential in the digital age, as successful communication depends not only on what is written but also on how messages are interpreted within specific social and technological contexts.
Keywords: Keywords: Pragmatics, Digital Communication, Online Discourse, Meaning-Making, Emojis, Speech Acts, Context, social media